Pelatihan Pembuatan Makanan Pendamping untuk Anak dan Bayi dalam Mencegah Stunting - Ni Wayan Oktarini Anthonia Candra Dewi; Arvinda C.Lalang; Lolita A.M. Parera (Universitas Nusa Cendana, 2022)
This program is carried out to provide information and alternative solutions to the current problem, namely the high stunting rate in Kupang Regency. Socialization about stunting is very important so that the community, especially pregnant women and mothers with toddlers and toddlers can pay close attention to the nutritional intake they eat. The method used is through socialization activities and the practice of making complementary foods by the participants. The practice of making complementary foods for children and infants in preventing stunting is aimed at enabling parents to process complementary foods using materials that are easily available and affordable and without preservatives. Complementary food processing must contain sufficient carbohydrates, proteins, fats, vitamins and minerals. This service program activity was very well received by the participants and the participants finally understood the dangers of stunting in children's development and were able to practice making complementary foods using food ingredients that can be obtained from the surrounding environment.